PRE-SERVICE MATHEMATICS TEACHERS’ SYMBOL SENSE BEHAVIOR: THE CASE OF EQUATIONS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2021)
Symbol sense refers largely to an ability to give meaning and to see important structures in symbols, expressions, formulas, and equations. This ability shows an algebraic proficiency in dealing with symbolic representations and is considered important for pre-service mathematics teachers for their future careers. This study aims to investigate pre-service mathematics teachers’ symbol sense ability when dealing with equations. To do so, we set up a qualitative case study. First, after conducting a literature study, we designed symbol sense tasks according to symbol sense characteristics on the topic of equations. Second, we administered an individual written test involving 31 pre-service mathematics teachers (18-19-year-old) at the beginning of the School Mathematics course. Third, we analyzed written work using a symbol sense perspective. The results showed that about two-thirds of the participants lacked symbol sense since they tend to use more procedural strategies than symbol sense strategies in solving equations.
Keywords: symbol sense; equations; pre-service mathematics teachers; algebra education